DETERMINATION OF NITRAZEPAM IN PHARMACEUTICAL PREPARATIONS USING SOLID-PHASE REACTOR - REVERSE FLOW INJECTION ANALYSIS - Jamal, Mariam; Hadi, Hind (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: A simple and fast reverse flow injection system including a solid-phase reactor containing PbO2 with spectrophotometric detection was suggested for the determination of nitrazepam (NIT) in pharmaceutical tablets. Methods: The method was based on oxidation of the reagent (phloroglucinol) with PbO2 immobilized in a polymeric matrix which was then coupled with reduced NIT in aqueous medium. The pink-colored product was measured at 530 nm. Results: The calibration graph was linear over the range of 50–400 μg/mL with a relative standard deviation of <2% (n=29) and a sample throughput of 48 samples per hour. The variables of the solid-phase reactor such as composition, particle size, and length of the reactor were studied. The chemical and physical parameters, which affect the reverse flow method, were also studied. Conclusion: The oxidation reactor engaged with a flow system was successfully applied for the determination of NIT with good sensitivity and precision.